(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
The Treaty for friendship, good-neighbourliness and cooperation between the Republic of Macedonia and the Republic of Bulgaria was 41nrolment in Skopje, on 1 August, 2017. The treaty still causes legal and political controversies regarding the legality and erasure of the Macedonian nation, language, history and culture. Hence, the question that I am exposing is interesting and important for the Macedonian people and Macedonian state and for interesting of the International law from the aspect of its content and a way the legal principles spill over into Political ones